Using the flow of conjectural information for short term forecasting of economic activity in Argentina - D'Amato, Laura (2009)
We exploit the richness of a large data set of daily and monthly business cycle indicators by combining them to produce nowcast of contemporaneous real GDP growth as well as forecast. Nowcast outperforms two benchmark models: the one-quarter ahead forecast of an AR(1) in the previous quarter and previous quarter actual value of GDP growth used as current value predictor. When we combine indicators to produce forecasts, the RMSE forecast pooling outperforms the AR(1) benchmark model predictions at the 3, 6 and 12 month horizons. The methodology offers a valuable approach for providing timely information for policy decision making.